Análise comparativa da ação antimicrobiana dos cimentos endodônticos Acroseal, Sealapex e AH plus pós presa em biofilme de enterococcus faecalis - Rezende, Gabriely Cristinni [UNESP] (2015)
Enterococcus faecalis is a gram positive bacteria that can resist to the endodontic therapy and maintain the infection present in the root canal system. Therefore, the use of endodontic sealers with antimicrobial activity could help to eliminate residual microorganism that have survived after endodontic treatment. The present study aimed to compare the antimicrobial activity of the endodontic sealers Acroseal, Sealapex and AH Plus in vitro biofilm model. It were prepared 144 bovine dentin specimens, twelve blocks for each cement in each experimental time that remained in plates containing culture medium inoculated with E. faecalis (ATCC 51299) for biofilm formation. After 14 days, the samples were transferred to another plate with test sealers and were kept at 37oC and 5% CO2 for 2, 7 and 14 days. Specimens without sealers were used as a control for each period. After each experimental, the samples were agitated in sonicator. The suspensions were agitated in vortex and serially diluted in saline and triple plaqued in m-Enterococcus agar. Colony forming unit were counted and the data were statistically analyzed using ANOVA, Shapiro-Wilk and Kruskal-Wallis one-way test (p<0.05) for the antimicrobial potential determination. Results: Sealapex showed significant difference in all experimental times in comparison to all other groups. AH Plus and Acroseal showed antimicrobial activity just at 14th experimental day. Conclusion: Neither of sealers setting tested was able to remove biofilm . The Sealapex showed higher antimicrobial activity in all experimental periods. All sealers examined the antimicrobial effectiveness was higher with over time